THE IMPORTANCE AND PERFORMANCE ANALYSIS OF EMPLOYEE WELFARE PROGRAM CASE STUDY AT PT. PLN (PERSERO) REGION SULUTENGGO - Lamongi, Ariens L. W. (Sam Ratulangi University, 2015)
ABSTRACT In the workplace, employees can greatly affect the entire business performance. So, many business companies must provide a program that can increase the work quality of their employee, one of them is Employee Welfare. The objectives in this research is to know importance and performance of employee welfare program in PT.PLN. Results base on Importance Performance Analysis, which are: Health care, compensation, increase regular salary rankings, promotion position, and compensation retirement are located in quadrant I (high importance low performance), Leave and residential allowance for employees are located in quadrant II (high importance high performance), Absent work permit, aid for employee decease, aid for office accident, aid for damages goods and property are located in quadrant III (low importance low performance), Periodical basic salary increase, increase salary rank of devotion, substitute residential facilities, loan assistance home ownership, transportation allowance, and awards are located in quadrant IV (low importance high performance). Â Keywords: Importance and Performance Analysis, Employee Welfare.